EFEKTIVITAS MODEL LATIHAN PASSING DIAMOND DAN MODEL LATIHAN PASSING TRIANGLE TERHADAP AKURASI PASSING PERMAINAN FUTSAL PADA EKSTRAKURIKULER DI SMAN 1 JALAKSANA TAHUN 2024 - Agustin, Deni; Hana Astria Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The effectiveness of the diamond passing training model and the passing triangle training model on the accuracy of futsal extraculicular passing passing for the boys at SMA N 1 Jalaksana in 2024. The purpose of this study was to determine: . The effectiveness of the diamond passing training model and the passing triangle training model on the accuracy of futsal extraculicular passing passing for the boys at SMA N 1 Jalaksana in 2024. “ This study used an experimental research methode with the research design used in this study, namely by using a two group pre-test and post-test design. The population of this study was 12 athletes. Determination of the sample using total sampling technique. The result of data analysis and processing showed that average passing of the diamond passing exercise was 32,58 and the passing triangle average was 35,08 which was tested for meaning using the t test and obtained t-count=1.098 with a significance value of 0,284 > 0,05 which means accepted. Thus there is difference in results, between the diamond and triangle passing training models in men’s futsal extraculicular activities at SMA N 1 Jalaksana in 2024. Judging from the average, it shows that the triangle passing training models has a greater effect than diamond passing on a acuracy of men’s futsal extraculicular activities. Jalaksana Senior High School in 2020.